Pay to win? Exploring medical students’ use of, and access to, paid commercial educational resources - Michaela Vernon; Nadin Hawwash; Enam Haque; Harish Thampy (BMC Medical Education)
Abstract Background Medical students are often driven by assessment-focused outcomes, aiming not only to pass and progress but also to enhance their academic rankings and achieve awards that influence future recruitment in a highly competitive job market. Consequently, there is growing reliance on the rapidly expanding range of commercial educational resources. However, these resources typically require paid subscriptions, creating barriers for students, particularly those from widening participation backgrounds. This study examines the support medical schools provide for paid commercial educational resources and explores medical students’ perceptions of these resources, with a focus on potential inequities. Methods Two separate questionnaires were utilised. The first was distributed to assessment leads at all UK medical schools to determine whether formal guidance or funding for paid resources was provided. The second was sent to all 915 Year 3 and Year 4 students at our medical school to assess their annual expenditure on paid commercial resources, frequency of use, perceived impact on examination outcomes, and attitudes toward the integration of these resources into their studies. Results Thirty out of 43 (70%) medical schools completed the first questionnaire. Half provided guidance on paid resources, and seven offered funding support. Schools expressed concern about the quality assurance process in place for commercial paid-for platforms and the risks this could pose for students’ learning. Ninety-nine out of 915 (10.8%) medical students responded to the second questionnaire; 96% reported paying for online resources, on a background of 64% expressing general financial concerns. These resources were widely used, considered essential for success in summative assessments, and perceived as a cultural norm among medical students. Students also acutely recognised the inequities that use of these commercial resources created within their peer group. Conclusions Medical schools should recognise the ubiquitous use of paid-for commercial resources among their students and the consequent inequities, which may disproportionately impact individuals from disadvantaged backgrounds. We recommend medical schools provide their students with guidance on the potential benefits and pitfalls of commercial resources, including the development of skills to appraise content critically. Additionally, institutions should explore strategies to mitigate disparities in access, ensuring that all students, irrespective of their socioeconomic status, are afforded equitable opportunities to succeed.